IgM Antibody Repertoire Fingerprints in Mice Are Personalized but Robust to Viral Infection Status - Yermanos, Alexander; Kräutler, Nike Julia; Pedrioli, Alessandro; Menzel, Ulrike; Greiff, Victor; Stadler, Tanja; Oxenius, Annette; Reddy, Sai T. (Frontiers in Cellular and Infection Microbiology, 2020)
Antibody repertoire sequencing provides a molecular fingerprint of current and past pathogens encountered by the immune system. Most repertoire studies in humans require measuring the B cell response in the blood, resulting in a large bias to the IgM isotype. The extent to which the circulating IgM antibody repertoire correlates to lymphoid tissue-resident B cells in the setting of viral infection remains largely uncharacterized. Therefore, we compared the IgM repertoires from both blood and bone marrow (BM) plasma cells (PCs) following acute or chronic lymphocytic choriomeningitis virus (LCMV) infection in mice. Despite previously reported serum alterations between acute and chronic infection, IgM repertoire signatures based on clonal diversity metrics, public clones, network, and phylogenetic analysis were largely unable to distinguish infection cohorts. Our findings, however, revealed mouse-specific repertoire fingerprints between the blood and PC repertoires irrespective of infection status.